2018
DOI: 10.3390/genes9010036
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding for Repair: Understanding Molecular Functions of the SMC5/6 Complex

Abstract: Chromosome organization, dynamics and stability are required for successful passage through cellular generations and transmission of genetic information to offspring. The key components involved are Structural maintenance of chromosomes (SMC) complexes. Cohesin complex ensures proper chromatid alignment, condensin complex chromosome condensation and the SMC5/6 complex is specialized in the maintenance of genome stability. Here we summarize recent knowledge on the composition and molecular functions of SMC5/6 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 120 publications
(216 reference statements)
0
56
0
Order By: Relevance
“…One additional copy of SMC5 was located on the B genome (three copies total in the allohexaploid), whereas RAD51 and SYN4 were predicted to be present in seven and eight copies, respectively. The SMC5 protein in complex with SMC6 is involved in DNA double‐strand break repair (Diaz & Pecinka, ), whereas SYN4 controls chromosome alignment and especially cohesion of chromatin arms and centromeres during meiosis in Arabidopsis thaliana (Schubert, ). Mutation of SYN4 results in an increase of chromosome bridges during anaphase, leading to the abortion of pollen development (Schubert et al ., ), and hence could potentially have affected fertility in our study; however, the presence of eight copies of this gene also may preclude a visible phenotype (although how many of these gene copies are functional, or function in meiosis, is unknown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One additional copy of SMC5 was located on the B genome (three copies total in the allohexaploid), whereas RAD51 and SYN4 were predicted to be present in seven and eight copies, respectively. The SMC5 protein in complex with SMC6 is involved in DNA double‐strand break repair (Diaz & Pecinka, ), whereas SYN4 controls chromosome alignment and especially cohesion of chromatin arms and centromeres during meiosis in Arabidopsis thaliana (Schubert, ). Mutation of SYN4 results in an increase of chromosome bridges during anaphase, leading to the abortion of pollen development (Schubert et al ., ), and hence could potentially have affected fertility in our study; however, the presence of eight copies of this gene also may preclude a visible phenotype (although how many of these gene copies are functional, or function in meiosis, is unknown).…”
Section: Discussionmentioning
confidence: 99%
“…RAD51 is one of the most‐studied proteins involved in double‐strand repair during meiosis, and multiple paralogues of this gene are expressed together with DMC1 to form protein complexes in Arabidopsis which regulate crossover formation (Schubert, ). Mutation of paralog RAD51B has been shown to reduce homologous recombination (Diaz & Pecinka, ). Other studies showed no significant effect on mutation of RAD51 on the number of crossovers observed during meiosis (Schubert et al ., ), but RAD51 has previously also been implicated in promoting noncrossover events (Schubert, ) and linked to homology recognition in maize (Pawlowski et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Key factors establishing and orchestrating chromosome organization are STRUCTURAL MAINTENANCE OF CHROMOSOME (SMC) complexes: cohesin (containing SMC1 and SMC3), condensin (containing SMC2 and SMC4), and the SMC5/6 complex (containing SMC5 and SMC6; reviewed in Hirano, 2006;Jeppsson et al, 2014b;Uhlmann, 2016). The heterodimeric SMC backbone serves as a structural component and a docking platform for additional subunits that vary depending on the complex, thereby enabling a variety of specific assemblies (reviewed in Kegel and Sjögren, 2010;Diaz and Pecinka, 2018). Studies in yeasts and animals showed that cohesin facilitates sister chromatin cohesion, and condensin I and II complexes mediate large-scale chromatin folding and chromosome condensation (reviewed in Hirano, 2012;Uhlmann, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The arm region in‐between is made up by a coiled‐coil structure, which in SMC5 is unique in the way that it mediates binding to the Nse2 subunit, a SUMO E3 ligase of the SP‐RING family. Nse2‐dependent sumoylation is essential for the maintenance of chromosome integrity (Stephan et al , ; Uhlmann, ; Zilio et al , ; Diaz & Pecinka, ).…”
Section: Dna‐dependent Sumo E3 Ligase Activation Of the Nse2‐smc5‐6 Cmentioning
confidence: 99%
“…The arm region in-between is made up by a coiled-coil structure, which in SMC5 is unique in the way The EMBO Journal 37: e99705 | 2018 that it mediates binding to the Nse2 subunit, a SUMO E3 ligase of the SP-RING family. Nse2-dependent sumoylation is essential for the maintenance of chromosome integrity (Stephan et al, 2011;Uhlmann, 2016;Zilio et al, 2017;Diaz & Pecinka, 2018). SUMO conjugation to its target proteins is executed by the sequential action of E1activating, E2-conjugating, and E3-ligating enzymes.…”
mentioning
confidence: 99%